Increasing N2200 Charge Transport Mobility to Improve Performance of All Polymer Solar Cells by Forming a Percolation Network Structure - Yan, Ye; Liu, Yadi; Zhang, Qiang; Han, Yanchun (Frontiers in Chemistry, 2020)
The poor electron transport ability of the polymer acceptor is one of the factors restricting the performance of all-polymer solar cells. The percolation network of conjugated polymers can promote its charge transfer. Hence, we aim to find out the critical molecular weight (MW) of N2200 on the forming of the percolation network and to improve its charge mobility and thus photovoltaic performance of J51:N2200blend. Detailed measurements demonstrate that when the MW of N2200 is larger than 96k, a percolation network structure is formed due to the chain tangled and multi-chain aggregations. Analysis of kinetic experiments reveals that it is the memory of the N2200 long chain conformation and the extent of aggregation in solution are carried into cast films for the formation of the percolation network. Thus, the electron mobility increases from 5.58×10 -6 cm 2 V -1 s -1 (N220017k) to 9.03×10 -5 cm 2 V -1 s -1 when the MW of N2200 is greater than 96k. It led to a balance between hole and electron mobility. The µh/µe decrease from 16.9 to 1.53, causing a significant enhancement in the PCEs, from 5.87 % to 8.28 % without additives.